The unique family law in the state of Israel - Kohen, Yitsḥaḳ (Touro University Press, 2021)
Inthe State of Israel, the unique family law derives from ancient Jewish law, halakhictraditions, and an extensive legal tradition spanning many centuries and locations. This comparative study covers topics such as issues subject to modification, the right of a minor toindependent status, extramarital relationships, and joint property.